Fast Disintegrating Tablets of Olmesartan Medoxomil Using Solid Dispersion Technique - Mali, Rahul K. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Olmesartan medoxomil (OLM) is a poorly soluble drug and its low aqueous solubility leads to poor dissolution and bioavailability. The aim of this work was to improve the solubility of poorly aqueous soluble drug OLM by solid dispersion (SD) technique. Materials and Methods: A phase solubility study was performed to determine the effect of various polymers on aqueous solubility of drug. The binary SD of OLM was prepared by using poloxamer 407. The SDs were prepared by kneading, melting and solvent evaporation (SE) method by varying drug to carrier ratio. The optimized SD formulations were characterized by Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and powder X-ray diffraction (XRD). Fast disintegrating tablets (FDTs) of OLM were formulated using optimized SD. The in vitro evaluation of FDTs was done including stability studies. Results: Phase solubility study indicated 5.3 fold increase in solubility of OLM by Poloxamer 407. The results of FTIR, DSC, SEM, and XRD study showed the conversion of crystalline form of OLM to amorphous form. The results revealed that SD prepared by SE method showed rapid dissolution as compared to other methods. The FDTs of optimized SD containing croscarmellose sodium showed faster and complete in vitro drug release within 20 min. Formulation M6 was found to be optimized formulation owing to its 84.09 dissolution efficiency, 4.82 min mean dissolution time and 100% drug release. Optimized formulation was found to be stable for 3-month period. Conclusion: The results conclusively confirmed successful improvement in dissolution of poorly water-soluble drug OLM.